(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
In today’s world of globalization, Organizations face enormous pressures from various stakeholders of the business environment. The dynamism in the environment has created threats and opportunities to all modern day organizations. So, the managers have to look for finding the best possible ways of striking a balance between the expected and the actual.Post-graduation education in professional courses especially in management in India stands at a turning point. Without change, the traditional design of educating the business leaders of future is likely to be far behind in the competitive and dynamic global economy. In order to offer our students with the qualifications needed to compete in this market, experts required to recognize and accept the challenges of up gradation. The complexities in upcoming trends at markets must be incorporated into the post graduate management educational framework. The presence of an institution is depend upon the placement opportunity and the kind of education given with updated pedagogy. As academics, need to accept the challenges before us today, there is no reason teachers in India cannot retain our position as the high-quality educational services for decades to come. There for it is immediate need to align the education in Management as per the requirement of Nation as well globe.This research paper emphasis on to find out the current education system pertinent to the management education, simultaneously to find out ways for value improvement in the present management education system to current challenges.